2011
DOI: 10.1002/jsfa.4555
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethylene, cytokinin and physical treatments on BoPaO gene expression of harvested broccoli

Abstract: A close correlation between chlorophyll degradation and BoPaO expression was found during broccoli senescence. This relationship was corroborated in samples treated with different hormonal and physical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 37 publications
3
27
0
13
Order By: Relevance
“…This might explain why the ratio of chlorophyll-a to chlorophyll-b in YL was the lowest. It has been widely reported in the literature that PAO encodes a Rieske-type monooxygenase, which explicitly catalyzes the oxidation of pheophytin a [81][82][83][84][85][86]. PAO activity provides the structural basis for all further breakdown products that are essential for the aging of leaves to yellow.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain why the ratio of chlorophyll-a to chlorophyll-b in YL was the lowest. It has been widely reported in the literature that PAO encodes a Rieske-type monooxygenase, which explicitly catalyzes the oxidation of pheophytin a [81][82][83][84][85][86]. PAO activity provides the structural basis for all further breakdown products that are essential for the aging of leaves to yellow.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that chlorophyll loss of broccoli florets is associated with ethylene production in the vegetable or ethylene accumulation during storage (Chen et al, 2008;Tian et al, 1995;Costa et al, 2005;Gómez-Lobato et al, 2012a). Inhibiting ethylene production (Henzi et al, 1999) or ethylene action (Ku and Wills, 1999;Fernández-León et al, 2013;Gómez-Lobato et al, 2012b) can delay yellowing of broccoli.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that ethylene seems to be the principal promoter in senescence and yellowing of the broccoli after harvest as chlorophyll loss is associated with an increase in ethylene production in florets (Tian et al, 1995;Ku and Wills, 1999;Henzi et al, 1999). Chlorophyll degradation of broccoli is accelerated by dipping the vegetable in ethephon solution (releasing ethylene) (Costa et al, 2005;Gómez-Lobato et al, 2012a). Yellowing of broccoli is also increased as the 1-aminocyclopropane-1-carboxylic acid (ACC) level increases, which can lead to increase in ethylene formation (Pogson et al, 1995;Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As a climacteric fruit, papaya exhibits rapid softening and has a short-term shelf life, which significantly limits its market value (Jain et al, 2011 ). The elucidation of how endogenous hormones function in postharvest decay under different conditions is therefore of importance not only to plant biologists but also to agronomists (Gomez-Lobato et al, 2012 ; Chen et al, 2016 ). However, little is known of the roles of endogenous auxin in the postharvest maturation of papaya fruit.…”
Section: Introductionmentioning
confidence: 99%